2017
DOI: 10.3389/fpls.2017.00078
|View full text |Cite
|
Sign up to set email alerts
|

An RNA-Seq Analysis of Grape Plantlets Grown in vitro Reveals Different Responses to Blue, Green, Red LED Light, and White Fluorescent Light

Abstract: Using an RNA sequencing (RNA-seq) approach, we analyzed the differentially expressed genes (DEGs) and physiological behaviors of “Manicure Finger” grape plantlets grown in vitro under white, blue, green, and red light. A total of 670, 1601, and 746 DEGs were identified in plants exposed to blue, green, and red light, respectively, compared to the control (white light). By comparing the gene expression patterns with the growth and physiological responses of the grape plantlets, we were able to link the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
69
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 78 publications
9
69
1
3
Order By: Relevance
“…Blue light reportedly improved 5aminolevulinic acid synthesis in tobacco callus cells (Kamiya et al, 1983) and Chinese cabbage (Fan et al, 2013a), which is the key precursor in the chlorophyll biosynthetic pathway, followed by the conversion into protoporphyrin IX. Li et al (2017) reported blue light increased the expression of the genes encoding the heme-binding 2-like protein and chloroplast early light-induced protein, which may increase chlorophyll accumulation and promote chloroplast development in grape in vitro propagation. Once exposed to narrow-bandwidth B light, decreased L* values were detected in the coleus leaves, although they were not significant (Table 3), and similar results were reported that the wavelength from 400 to 500 nm produced darker, less chromatic pear fruits (Dussi et al, 1995).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Blue light reportedly improved 5aminolevulinic acid synthesis in tobacco callus cells (Kamiya et al, 1983) and Chinese cabbage (Fan et al, 2013a), which is the key precursor in the chlorophyll biosynthetic pathway, followed by the conversion into protoporphyrin IX. Li et al (2017) reported blue light increased the expression of the genes encoding the heme-binding 2-like protein and chloroplast early light-induced protein, which may increase chlorophyll accumulation and promote chloroplast development in grape in vitro propagation. Once exposed to narrow-bandwidth B light, decreased L* values were detected in the coleus leaves, although they were not significant (Table 3), and similar results were reported that the wavelength from 400 to 500 nm produced darker, less chromatic pear fruits (Dussi et al, 1995).…”
Section: Discussionmentioning
confidence: 96%
“…4C), and Li et al (2010) reported similar results with cotton leaf tissue culture. Plant height and root growth were reduced in response to the blue light treatment in grape in vitro culture, possibly due to the blue light-induced down-regulation in the expression of the auxin-repressed protein gene, which made the endogenous auxin exceed the optimal level (Li et al, 2017). The compactness of seedlings could be a desirable characteristic so blue light treatment would be benefit for some specific plant production methods (Wollaeger and Runkle, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Chl a /Chl b levels increased in Hoe29, but decreased in Augster Weiss and Müller-Thurgau. This higher Chl a /Chl b ratio in Hoe29 further suggests that this genotype is well adapted to UV irradiation (Li et al 2017). In addition, the changes in Chl a levels were greater than were the change in Chl b , indicating that the overall changes in chlorophyll content in response to UV-C are mainly a consequence of Chl a production.…”
Section: Changes In Chlorophyll Contents Correlates With the Resistanmentioning
confidence: 88%
“…The LED-B (R:B = 8:1) increased plant height and stem diameter of the pepper plants more than the LED-A [10].With the progress of "next-generation" sequencing technology, transcriptome technology has been widely used to study the response of plants to the environment [11]. In grape plantlets under blue and red light treatments, the blue light induced the upregulation of genes related to microtubules, serine carboxypeptidase, and chlorophyll synthesis, but downregulated auxin-repressed protein and resistance-related genes [12], whereas red and green light promoted the expression of the auxin inhibitor protein gene, suggesting that the auxin concentrations are low in plants treated with red and green light, a condition that is suitable for plant stem and root length growth. Transcriptome sequencing of Saccharina japonica under blue light (notation by Swissprot, Nr, GO, KEGG, and COG databases) found that unigenes are putative BL photoreceptors; these genes are involved in processes of circadian rhythm, flavonoid biosynthesis, photo-reactivation, and photo-morphogenesis [13].Several authors have reported that the application of supplementary light improves the growth and development of vegetables, fruits, and ornamental plants under greenhouse conditions [14][15][16].…”
mentioning
confidence: 99%